Narrate and communicate. Forms and practices for teaching history - Simona Salustri (Didattica della storia, 2020)
History as a discipline is called to face the progressive erosion of its value within contemporary society. In order to achieve this goal, history must adapt itself to the rapid evolution of the media. Also, Didactics of History needs to change and to answer multiple questions: How has the relationship with the present changed today, especially for young people? What are the new and old forms of communication that can integrate Didactics of History? Which kind of sources and themes can help to adapt Didactics of History to nowadays challenges? This essay tries to answer these questions through a critical reading of the papers submitted to the panel Narrare e Comunicare at the conference Viva la storia Viva. La storia è il faro dell’umanità.